Kesantunan Tindak Direktif pada Tuturan Anak dan Orang Tua di Desa Ngumbul, Kabupaten Pacitan - nfn Hestiyana (Madah: Jurnal Bahasa dan Sastra, 2018)
of politeness of directive acts on parents' speech in Ngumbul Village of Pacitan Regency, and the scope of the directive acts on the children's and parent's speech in Ngumbul Village of Pacitan. This research uses descriptive method with qualitative approach. The object of research is the politeness of directive acts on the speech of children and parents in Ngumbul Village, Pacitan regency, East Java. The data in this study are oral data or interviews of adolescents aged 12—15 years old and parents conducted in December 2017. Techniques of collecting data are done in stages, namely: first, held the data collection directive acts on children's speech to their parents colected. In collecting the data recorder and sheet observation format (observation) and field notes are used. The recording was  transcribed and analyzed based on the theory used. Based on the results of the analysis, it can be concluded that there are 8 directive acts, namely: asking, commanding, advising, rebuking, inviting, suggesting and, persuade, in the form of politeness directive acts on the child's speech to his parents, Then, there are 6 directive acts, namely: asking, commanding, advising, suggesting, interrogating, and scolding. in the manner of the directive act  on the parent's speech to the children. Furthermore, there are 5 scale of politeness, namely: cost-benefit scale, optionality scale, indirectness scale, authority scale, and social distance scale in the scale of politeness of directive acts on children's and parent's speech in Ngumbul Village of Pacitan Regency